Elena and the secret of Avalor [videorecording (DVD)] (Walt Disney Home Video, 2017)
See how it all began, and discover the secret behind the legend of Disney's most inspiring new Crown Princess! Frozen in time and trapped inside the Amulet of Avalor for over forty years, Elena has finally found the one brave princess who can set her free: Sofia! Together with magical flying jaquins, spirit animal Zuzo, and young wizard-in-training Mateo, Princess Elena must unite her people, battle the evil Queen Shuriki, and reclaim her throne.